User Experience Analysis of Adobe Lightroom Application for Photographers Using the Heart Framework Method - Hamdi, Fathan Surya; Syaifullah, Syaifullah; Saputra , Eki; Jazman, Muhammad (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Adobe Lightroom is a very popular software among photographers for editing and organizing photos. Although the application is feature-rich and intuitive, many users still face various problems using it. Common issues include slow performance on older hardware, synchronization difficulties between devices, a complex interface, and feature limitations. These issues can interfere with user productivity and satisfaction, especially for photographers who depend on this application for their work. In addition, the Adobe Lightroom subscription fee is also a barrier for photographers. This research aims to analyze the user experience of Adobe Lightroom using the HEART Framework method, which was developed by Google to evaluate the quality of user experience (UX) based on five dimensions namely Happiness, Engagement, Adoption, Retention, and Task Success. Research instrument testing uses validity and reliability test calculations which state that each statement item for user-centered metrics has been said to be valid and reliable. The achievement of the level of usability of the user experience of the Adobe Lightroom application has met and exceeded the predetermined goals in the goals-signal-metrics with a variable value of Happiness of 84.2%, Engagement of 79.3%, Adoption of 62.8%, Retention of 79%, and Task Succes of 83.5%. This result shows that the Adobe Lightroom application has created a positive experience for its users, but further development is still needed to provide a more optimal user experience in the future.